Variational and PDE-based methods for image processing - Duan, Jinming (2018)
In this thesis, we study modern variational and partial differential equation (PDE)-based methods for three image analysis applications, namely, image denoising, image segmentation, and surface reconstruction from point clouds. A common feature these applications have is the use of novel variational formulations.